A review of bio-based activated carbon properties produced from different activating chemicals during chemicals activation process on biomass and its potential for Malaysia - Chew, Tung Woey; H’Ng, Paik San; Luqman Chuah Abdullah, Chuah Teong Guan; Chin, Kit Ling; Lee, Chuan Li; Mohd Nor Hafizuddin, Mohd Sahfani; TaungMai, Lulu (Multidisciplinary Digital Publishing Institute, 2023)
Activated carbon is the preferred adsorbent for gas and water treatment in various industry across the world due to its efficiency, reliability, and accessibility. Recently, in Malaysia, studies are mainly focused on the fabrication of activated carbon from lignocellulosic biomass-based precursors from agricultural waste such as coconut shell, rice husk, and palm kernel shell. Activated carbon fabrication is a two-step process; the precursor will first undergo carbonization, then, activation is carried out either physically or chemically to develop its porous surface for adsorption purposes. The main benefit of activated carbon is the customizable pore structure for different utilization, which can be easily achieved by the chemical activation process. The types and concentration of chemicals used for activation, pre-treatment of precursor, duration of the activation process, and the mass ratio of precursor to chemicals are proven to effectively influence the resulting pore structure. However, the chemicals used in the activation process can be harmful to the environment. Thus, the chemical recovery process is necessary after the activation process. Nonetheless, more in-depth research on producing activated carbon from abundant biomass materials with bio-based chemical agents for activation is needed to achieve an ecological and sustainable manufacturing process.